"Espíritus sobre las ruinas": Wittgenstein y el pensamiento estético - Krebs, Victor (1998)
Paying special attention to his reflections on a esthetics, it is held in this paper that the later Wittgenstein, far from rejecting the"transcendent" from his philosophical discourse as he is usually read, aims rather at recovering it and giving it a new meaning. He thus responds to a real need in the philosophical thought that continues to define itself, even in this century, in terms of criteria of knowledge that are alíen to it. Specifically, it is argued that the Wittgensteinian recourse to the invention of "intermediatec ases" and fictional "natural histories" achieves this goal by activating other modes of awareness that relocate the transcendent within philosophical thinking without appealing neither to the supernatural realm nor to a mystical knowledge or insight.